1974
DOI: 10.1002/kin.550060104
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of halogens with hydrogen halides. Studies in the Cl2 + HBr system

Abstract: The following net processes occur in a system containing chlorine and hydrogen bromide :(1)These reactions have been followed spectrophotometrically in a gas phase stopped flow apparatus. The first two reactions are strongly surface catalyzed on untreated glass or quartz, but are much slower if the cell surface has been covered with silicone and photochlorinated. Rates in such systems are first order in each reactant, and comparable limiting rate constants have been obtained in cells with different methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This would imply that if klc is lo4 to lo5 M-' s-l then k6 would be lo8' to 108.5 M-1 s-These are not unreasonable values for these rate constants [16,20,21]. However, even 30 torr of HBr, the lowest pressure of HBr added, would be at least 100 times the steady state pressure and would completely quench the autocatalysis.…”
Section: (V)mentioning
confidence: 99%
“…This would imply that if klc is lo4 to lo5 M-' s-l then k6 would be lo8' to 108.5 M-1 s-These are not unreasonable values for these rate constants [16,20,21]. However, even 30 torr of HBr, the lowest pressure of HBr added, would be at least 100 times the steady state pressure and would completely quench the autocatalysis.…”
Section: (V)mentioning
confidence: 99%
“…Many experimental studies and quantum chemical calculations have been performed to reveal the mechanism of the reactions between halogens and halides 1–9. For example, an experimental investigation has been carried out on the reaction between Cl 2 and Br 2 and showed that the reaction happens through a bimolecular process 1, 2. The reaction F − +HCl→HF+Cl − was studied at the MP4/6‐31G* level and the rate constants at different temperatures were evaluated with the trajectory method 7.…”
Section: Introductionmentioning
confidence: 99%
“…A crucial piece of missing information is the shape of the potential surface for the approaching reagnets which is the determining factor 2 for the total reaction rate. 3 The purpose of this work is to provide a better understanding of the characteristic features of the entrance valley by investigating the temperature variation of the rate, the energy dependence of the reaction and the relative rates for two competing isotopically substituted reactions.…”
Section: 6mentioning
confidence: 99%